The survival guide for kids with autism spectrum disorder (and their parents) - Verdick, Elizabeth; Reeve, Elizabeth (Free Spirit Publishing Inc., 2021)
"This positive, straightforward book offers kids with autism spectrum disorder (ASD) their own comprehensive resource for both understanding their condition and finding tools to cope with the challenges they face every day"--